2021
DOI: 10.2147/opth.s315747
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Surgical Outcomes of Primary Angle-closure Glaucoma

Abstract: Purpose To evaluate surgical outcomes of the four common procedures utilized for primary angle-closure glaucoma (PACG). Methods A retrospective study of survival rate in surgical management of PACG was conducted in a referral eye center. One hundred and ninety-nine eyes from 173 PACG patients were collected for chart review. The procedures used were phacoemulsification (PE), combined PE with goniosynechialysis (PE-GSL), combined PE with trabeculectomy (PE-Trab), and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For decades, phacoemulsification and intraocular lens implantation (PEI) has been proposed for initial management of PACD [ 4 , 5 ]. PEI relieves pupillary block, deepening ACD and widening irido-corneal angle [ 6 ], while at the same time preserving the conjunctiva for future trabeculectomy if needed.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, phacoemulsification and intraocular lens implantation (PEI) has been proposed for initial management of PACD [ 4 , 5 ]. PEI relieves pupillary block, deepening ACD and widening irido-corneal angle [ 6 ], while at the same time preserving the conjunctiva for future trabeculectomy if needed.…”
Section: Introductionmentioning
confidence: 99%
“…XEN surgery, which belongs to the MIGSs, thus promising less complications, is gaining much attention nowadays 11 . Many studies have already reported on short- 12 , 13 , 14 and long-term follow-up following XEN implantation 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The procedure can separate the PAS from the angle under direct visualization, exposing the functional trabecular meshwork and restoring its filtering function. This procedure, combined with phaco under an endoscope for CACG, effectively lowers IOP and minimizes the postoperative complications of the filtering procedures [6][7][8] . Endocyclophotocoagulation (ECP; Endo Optiks, Little Silver, NJ, USA) was first reported by Uram in 1992 and delivers laser energy via an ab interno approach under direct visualization of ciliary processes [6] .…”
Section: Introductionmentioning
confidence: 99%